Prevalence of hygiene awareness during menstruation period among rural women of West Bengal, India - Bera, Shyamali; Adhikari, Anup (International Journal Of Community Medicine And Public Health, 2024)
Background: Menstruation is a physiological process of women. Reproductive infection during the menstrual period is a common phenomenon in women in rural areas of India. The present study was conducted to find out the prevalence of hygiene awareness in rural women of West Bengal. Methods: Fifty rural women from the West Medinipur District of West Bengal were studied. Questioner methods were followed to know the knowledge, attitude, and practice towards menstruation hygiene. Results: Proper knowledge of menstruation was absent in a large number of women but a large number of women (80%) took care of their hygiene during menstrual periods. 70% of women agreed to maintain personal hygiene to prevent reproductive-related diseases. 44% of women had a positive attitude towards the cleanness of genital areas with clean water whereas 56% of women did not show any interest. 96% of women change sanitary pads for 2-4 times a day to maintain menstrual hygiene. For disposing of used sanitary pads, 80% of women use home garbage areas whereas 20% of women use open fields outside the home. Conclusions: From the above study it could be concluded that hygiene awareness during the menstruation period among rural women of West Bengal, India is not satisfactory. Educational intervention is required.